THE EFFECT OF 5E LEARNING CYCLE INSTRUCTIONAL MODEL USING SOCIOSCIENTIFIC ISSUES (SSI) LEARNING CONTEXT ON STUDENTS’ CRITICAL THINKING - Cahyarini, A.; Rahayu, S.; Yahmin, Y. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
The aim of this study was to investigate the effect of 5E learning cycle instructional model using socioscientific issues (SSI) learning context on students’ critical thinking skills of acid-base. This study used quasi-experimental posttest only control group design. The sample consisted of three classes, which were XI MIA-4class (n = 32) that learned using 5E LC model, XI MIA-5 class (n = 33) that learned using 5E LC+SSI, and XI MIA-6 class (n = 32) that learned using conventional method. The samples were choosen by convenience sampling technique. The test instrument consisted of 15 multiple choice items which were valid and reliable (r = 0.806). The data were analyzed using one way ANOVA test and LSD posthoc test. The results of this study indicated that the students who learned using 5E LC+SSI model showed greater levels of critical thinking skills ( = 74,95) than both the student who learned using 5E LC model ( = 74,17) and the student who learned using conventional method ( = 68,96). Based on statistics analysis, there was significant differences on students’ critical thinkings between students taught using conventional method and students taught either using 5E LC+SSI model and 5E LC model. However, there was no significant differences on students’ critical thinking skills between students taught using 5E LC+SSI model and the students taught using 5E LC model.